The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11883-015-0554-1
|View full text |Cite
|
Sign up to set email alerts
|

HDL Cholesterol Efflux Capacity: Cardiovascular Risk Factor and Potential Therapeutic Target

Abstract: Low high-density lipoprotein cholesterol (HDL-C) levels are associated with incident cardiovascular events; however, many therapies targeting increases in HDL-C have failed to show consistent clinical benefit. Thus, focus has recently shifted toward measuring high-density lipoprotein (HDL) function. HDL is the key mediator of reverse cholesterol transport, the process of cholesterol extraction from foam cells, and eventual excretion into the biliary system. Cholesterol efflux from peripheral macrophages to HDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 56 publications
1
32
1
4
Order By: Relevance
“…In this sense, traditional risk factors reportedly explain only 3% of the variance observed in CEC [8]. Moreover, glucose tolerance status does not appear to impact CEC [28], and CEC cannot be explained by HDL cholesterol or apolipoprotein A-I levels [29]. Similarly, we did not find any association of statins with CEC in patients and control subjects.…”
Section: Discussionmentioning
confidence: 59%
“…In this sense, traditional risk factors reportedly explain only 3% of the variance observed in CEC [8]. Moreover, glucose tolerance status does not appear to impact CEC [28], and CEC cannot be explained by HDL cholesterol or apolipoprotein A-I levels [29]. Similarly, we did not find any association of statins with CEC in patients and control subjects.…”
Section: Discussionmentioning
confidence: 59%
“…First, several studies have shown an inverse association between the efficiency of patient plasma as a cholesterol acceptor in cholesterol efflux with the manifestation of various cardiovascular events. Cholesterol efflux capacity (CEC) of apoB‐depleted serum or plasma, measured in these studies, was a better predictor of CV events than HDL‐cholesterol (HDL‐C) (Bhatt and Rohatgi, ; Ogura et al, ; Rohatgi, ; Saleheen et al, ). Second, stimulation of the efflux resulted in the regression of atherosclerotic lesions (Bhatt and Rohatgi, ; Chyu and Shah, ; Fisher et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol efflux capacity (CEC) of apoB‐depleted serum or plasma, measured in these studies, was a better predictor of CV events than HDL‐cholesterol (HDL‐C) (Bhatt and Rohatgi, ; Ogura et al, ; Rohatgi, ; Saleheen et al, ). Second, stimulation of the efflux resulted in the regression of atherosclerotic lesions (Bhatt and Rohatgi, ; Chyu and Shah, ; Fisher et al, ). Despite the primary role of lipid‐free/lipid‐poor apoA‐I with preβ 1 ‐mobility in cholesterol efflux from macrophages, the atheroprotective significance of preβ 1 ‐HDL remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, there have been no reports investigating proteolytic cleavage of apoA‐I by primary human macrophages during physiological exposure, as occurs during cholesterol efflux, or its functional consequences. Such investigations are crucial, as several studies have emerged highlighting that improvement of HDL functionality may be more important than solely increasing HDL cholesterol levels to reduce CAD risk, as reviewed recently (20, 21).…”
mentioning
confidence: 99%